DEVELOPING ENTREPRENEURIAL HUMAN CAPITAL AMONG ISLAMIC BUSINESS STUDENTS: A LITERATURE REVIEW OF PSYCHOLOGICAL AND SPIRITUAL APPROACHES - Vida Maria Ulfa (Berajah Journal, 2026)
The development of entrepreneurial human capital through psychological and spiritual approaches among Islamic business students using the Literature Review method. This study is grounded in the urgency of developing entrepreneurial human capital that is not only oriented toward business competencies but also toward strengthening psychological capacity and spiritual values in facing contemporary economic dynamics. The research was conducted through the identification, selection, evaluation, and synthesis of reputable scientific articles published between 2018 and 2025. The findings indicate that psychological capital encompassing self-efficacy, optimism, resilience, and hope significantly contributes to the formation of entrepreneurial behavior among students. On the other hand, spiritual capital plays a role in fostering ethical orientation, the meaningfulness of business endeavors, and social responsibility grounded in Sharia values. The research findings also indicate a limited number of studies that integrate psychological and spiritual dimensions in the development of entrepreneurial human capital among Sharia business students. Therefore, this study offers an integrative conceptual model as a foundation for developing entrepreneurs who are adaptive, sustainable, and oriented toward Sharia business ethics.